Evaluation of an enzyme-linked immunosorbent assay for detection of antibodies to Junin virus in rodents - Morales, María Alejandra (2002)
Fil: Morales, María A. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Virales Humanas; Argentina.